2018
DOI: 10.1155/2018/3519247
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and Temozolomide in Neuroendocrine Tumor of Unknown Primary

Abstract: Incidence of low grade well-differentiated neuroendocrine tumors (NET) is on the rise. The North American Neuroendocrine Tumor Society estimates that the United States has more than 150,000 gastroenteropancreatic NET patients. About 10% of metastatic NETs can be unknown primary, and due to their rarity, dedicated treatment algorithms and regimens are not defined. Combination of capecitabine and temozolomide (CAPTEM) is one of the systemic treatments used in gastroenteropancreatic NETs. We explored clinical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…Peptide receptor radionuclide treatment in 60 GEP NET G3 patients resulted in PFS of 19 months and OS of 44 months [17]. Studies on temozolamide/ capecitabine treatment have reported RRs of 20-25% [22,23] and OS of 19 months [24], while everolimus led to PFS 6 months and OS 28 months in pancreatic NET G3 patients [25]. We found a PFS of only 5 months, and 28% progressed immediately on chemotherapy.…”
Section: Net G3mentioning
confidence: 50%
“…Peptide receptor radionuclide treatment in 60 GEP NET G3 patients resulted in PFS of 19 months and OS of 44 months [17]. Studies on temozolamide/ capecitabine treatment have reported RRs of 20-25% [22,23] and OS of 19 months [24], while everolimus led to PFS 6 months and OS 28 months in pancreatic NET G3 patients [25]. We found a PFS of only 5 months, and 28% progressed immediately on chemotherapy.…”
Section: Net G3mentioning
confidence: 50%
“…There are many retrospective and single-arm reports about CAPTEM use mainly in G1/G2 NETs of the pancreas [8,9,26,27], but data on G3 NENs is very limited. The confirmed efficacy of the CAPTEM regimen in G1/2 NETs encouraged attempts to treat G3 NETs in the second-line therapy [5] and in patients with Ki-67 >20% [9][10][11][12]. In the literature we found descriptions of outcomes of CAPTEM therapy in 18 patients with Ki-67 > 20% [9][10][11][12], and the treatment of NECs remains the domain of case reports [28].…”
Section: Discussionmentioning
confidence: 92%
“…There is no evidence from a randomised clinical trial on CAPTEM efficacy and safety. Data regarding the use of CAPTEM in G3 NENs is minimal, and neoplasms with Ki-67 > 20% into NETs and NECs were not differentiated in the literature reporting the use of CAPTEM [9][10][11][12]. Recently sunitinib was shown to be as effective for G3 NETs as for G1/2 NETs [13].…”
Section: Resultsmentioning
confidence: 99%
“…Retrospective studies of CapTem treatment included NET from different origins and found that CapTem has limited efficacy in non‐PanNET 20,21 . Al‐Toubah at al 22 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Retrospective studies of CapTem treatment included NET from different origins and found that CapTem has limited efficacy in non-PanNET. 20,21 Al-Toubah at al. 22 analysed 462 patients with NETs and showed that Patients with PanNET had the highest partial response rates and longest median PFS.…”
Section: Captem Therapy Is One Of the Few Standard Chemotherapies Inmentioning
confidence: 99%